The problems of logistics within the frame of European platform for transport research - Kabashkin, Igor (Journal of Business Economics and Management, 2004)
Review of the main research activities in the field of transport and freight logistics within the frames of European Research Area and European Platform for Transport Research.First Published Online: 14 Oct 2010